Needs Analysis on the Implementation of the Window Shopping Learning Model in Islamic Religious Education to Enhance Creative Thinking Skills - Dias Maulana (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study aims to analyze the application of the Window Shopping learning model in Islamic Religious Education (PAI) and Ethics subjects at SMP N 1 Cilacap. This study uses a descriptive qualitative approach with a field study type. The research subjects consisted of PAI teachers and ninth-grade students in class A. Data collection techniques were carried out through observation, interviews, and documentation. The results show that the Window Shopping model is implemented through the stages of planning, implementation, and evaluation of learning. The planning stage includes the preparation of lesson plans and teaching materials. In the implementation stage, teachers begin the lesson with an introduction, followed by group discussions, presentations of work, and “visiting” activities to observe and provide feedback on other groups' work. Evaluation was carried out through assessment for learning using observation and summative assessment techniques. The application of this model showed an increase in student activity, creativity, questioning skills, discussion participation, and understanding of the material. Thus, the Window Shopping model is considered effective in creating interactive and student-centered PAI learning.